Plasma medicine in Indonesian wound care: Clinical potential, implementation barriers, and practice recommendations - Warsono, Warsono; Kamaruddin, Mudyawati; Ahmad, Rasheed (Faculty of Nursing, Universitas Hasanuddin, 2026)
Both acute and chronic wounds remain significant challenges in Indonesian healthcare services. Postoperative wounds, diabetic ulcers, traumatic wounds, and infected wounds impose substantial clinical, financial, and psychosocial burdens on patients, families, and the healthcare system. The high incidence of non-communicable diseases, such as diabetes, limited availability of modern wound care facilities in many regions, and risk of nosocomial infections complicate the wound healing process and increase the length of hospital stay. Plasma medicine, particularly nonthermal plasma (cold atmospheric plasma), has emerged as an innovative approach to wound care. Nonthermal plasma can generate reactive oxygen and nitrogen species, electric fields, and low-dose UV radiation, all of which collectively contribute to antimicrobial effects, modulation of inflammation, and stimulation of tissue regeneration without causing thermal damage to healthy tissue (Kamaruddin et al., 2024). Various studies have shown that plasma-based wound therapy can reduce microbial load, improve granulation, and accelerate wound closure, particularly in chronic, hard-to-heal wounds.